Prevalence of AZFс Y chromosome microdeletions and association with spermatogenesis in Russian men from the general population - L. V. Osadchuk; G. V. Vasiliev; M. K. Ivanov; M. A. Prasolova; M. A. Kleshchev; A. V. Osadchuk (Вавиловский журнал генетики и селекции)
The Y chromosome contains a set of genes with testis-specific expression that are responsible for the development of testes and spermatogenesis, and it is the most important target in the search for genetic causes of male infertility. Most of these genes are located in the “azoospermia factor” AZF locus (regions AZFa, AZFb, and AZFc) on the long arm of the Y chromosome. Microdeletions of the Y chromosome, leading to the removal of the entire AZF locus as well as one or more regions (complete deletions), are one of the leading causes of spermatogenesis impairment and infertility. However, the role of partial AZFc deletions (gr/gr, b2/b3, b1/b3) in spermatogenesis failure is unclear, and their impact on spermatogenesis varies between populations. The aim of the present study was to assess the frequency of various types of AZFc microdeletions and to search for associations with spermatogenesis parameters in men of Slavic ethnicity from the general Russian population (n = 700, average age 25.8 years). To identify AZF microdeletions, the presence/ absence of 15 STS markers was analyzed using multiplex real-time polymerase chain reaction. Age, weight, height, and the volume, concentration, total count, proportion of motile and morphologically normal spermatozoa in the ejaculate were recorded for all participants. In the studied sample, 19.9 % (139/700) of men were found to have AZFc microdeletions, of which 16.7 % (117/700) were carriers of a partial b2/b3 deletion, 3.0 % (21/700) had a partial gr/gr deletion, and 0.14 % (1/700) had a complete b2/b4 deletion. Neither AZFa nor AZFb microdeletions nor other types of AZF deletions were detected. The overall frequency of all types of AZFc deletions, as well as each type of partial microdeletion, b2/b3 and gr/gr, did not differ in the groups of azoospermia, severe oligozoospermia (≤5.0 mill/ml), oligozoospermia (5.0 < SC < 16.0 mill/ml), and normal sperm concentration (≥16.0 mill/ml). Comparison of semen parameters in groups with different types of partial AZFc deletions and the control group (without deletions) also did not reveal significant differences. Thus, partial AZFc microdeletions b2/b3 and gr/gr do not have a significant impact on spermatogenesis in Slavic men. It is suggested that in Slavs, partial AZFc microdeletions b2/b3 and gr/gr are fixed in Y haplogroups N3 and R1a, respectively, and their negative impact on spermatogenesis is balanced by other genetic factors. The higher frequency of partial AZFc deletions (19.7 %) in Slavs compared to European populations (7.3 %) established in our study may be explained by the widespread distribution of these Y haplogroups in the Slavic population of Russia.